PENGEMBANGAN BAHAN AJAR TEMATIK BERBASIS INKUIRI TERBIMBING (GUIDED INQUIRY) UNTUK SISWA KELAS IV SEKOLAH DASAR (Studi pada Siswa Kelas IV SDN Sokosari 1 Tuban) - Agustin, Ina (JURNAL PENDIDIKAN DASAR NUSANTARA, 2017)
Abstract: The purpose of this research is (1) Produce teaching material thematically based guided inquiry (guided Inquiry) for the fourth grade students of elementary school, (2) Determine the level of validity, keterterapan, and the effectiveness of teaching materials thematically based guided inquiry (guided Inquiry) for graders IV Elementary School. The development model used in this study is a model developed by Borg & Gall. The thematic material in this reseach is able to solve the problems of the material used by the teacher of the class IV SDN Sokosari 1 Tuban, as the material relevant to students' characteristics, and in accordance with the living conditions of class IV SDN Sokosari 1 Tuban. Product material thematic form module thematic developed in compliance component as the material is good, so that the material this thematic can fill the availability and increasing the diversity of learning resources, particularly in the fourth grade SDN Sokosari 1 Tuban for use in the process of learning by teachers and students independent. Key words: thematic material, guided inquiry, elementary school Abstrak: Tujuan dalam penelitian ini adalah (1) Menghasilkan bahan ajar tematik berbasis inkuiri terbimbing (guided Inquiry) untuk siswa kelas IV Sekolah Dasar, (2) Mengetahui tingkat kevalidan, keterterapan, dan efektifitas bahan ajar tematik berbasis inkuiri terbimbing (guided Inquiry) untuk siswa kelas IV Sekolah Dasar. Model pengembangan yang digunakan dalam penelitian ini adalah model yang dikembangkan oleh Borg & Gall. Bahan ajar tematik mampu memecahkan permasalahan bahan ajar yang digunakan oleh guru kelas IV SDN Sokosari 1 Tuban, sebagai bahan ajar yang relevan dengan karakteristik siswa, dan sesuai dengan kondisi tempat tinggal siswa kelas IV SDN Sokosari 1 Tuban. Produk bahan ajar tematik yang berupa modul tematik yang dikembangkan telah memenuhi komponen sebagai bahan ajar yang baik, sehingga bahan ajar tematik ini dapat mengisi ketersediaan dan menambah keragaman sumber belajar khususnya di kelas IV SDN Sokosari 1 Tuban untuk digunakan dalam proses pembelajaran oleh guru dan siswa secara mandiri. Kata kunci: bahan ajar tematik, inkuiri terbimbing, sekolah dasar